Analisis Efektivitas Pemanfaatan Dana Zakat Bangun Sejahtera Indonesia (BSI) Maslahat Terhadap Program BSI Scholarship Di Universitas Jambi - Nur, Muhammad; Ridhwan, Ridhwan; Roihan, Muhammad (ILTIZAM Journal of Shariah Economics Research, 2025)
ABSTRACT In the history of the development of Islam, zakat has become the main source of funding for the government and plays a very important role in eradicating poverty, spreading Islam, developing education and culture, developing science, infrastructure, financing and building the military, and providing security and other social services. BSI Maslahat has various programs to distribute zakat funds, one of which is the BSI Scholarship Program. This program aims to provide educational assistance to students and students who are underprivileged but have high academic potential. The purpose of this study is to determine and analyze the effectiveness of the use of BSI maslahat zakat funds for the BSI scholarship program at the University of Jambi. The research method used is a qualitative-quantitative approach with descriptive analysis, which involves data collection through interviews, surveys, and documentation. The results of the study indicate that the use of zakat funds through the BSI Scholarship program has been effectively given to students who need to pay for education. The community sees this program as a form of BSI's commitment to supporting education and human resource development. The conclusion of this study confirms that a planned and directed program at BSI Maslahat, such as the BSI Scholarship, can be a strategic tool in building good education for students. Therefore, it is recommended that BSI continue to develop relevant and impactful BSI Scholarship programs, and conduct periodic evaluations to ensure their sustainability and effectiveness.